Head Injuries in Children — Quantitative and Qualitative analysis of Cases Regarding Children - Dorota Radlica; Sylwia Krzemińska; Adriana Borodzicz-Cedro; Marta Arendarczyk (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. With the development of civilization, there has been an increase of the percentage of head injuries cases in children. Head injuries are currently the third reason for the death of children under one year of age and first among older children. Aim. The aim of the study was the qualitative and quantitative analysis of head injuries among children admitted to the Hospital Emergency Ward in Trzebnica in 2010 as well as determination of factors, contributing to head injuries among children. Material and Methods. The statistical analysis regarded head injuries in children aged 0–18 which were reported to the Hospital Emergency Ward in Trzebnica within the period from January to December 2010. The total number of injuries reported was 315 and involved 118 girls and 197 boys. Results. The reason for accidents which resulted in children’s injuries were most often falls from height (27.0%), falls on the same level (24.4%) and hitting an object (21.6%). The reason for an accident is conditioned on the child’s age. The most common reason for injuries in children under 13 is a fall from height (30.8%) or a fall on the same level (28.5%). The accidents took place mainly during the day and in the summer period. In most cases in all age groups damage to epicrenium happened with children under 6 years of age. Conclusions. Head injuries are associated with age. They more often occur in the youngest group from 0 to 3 years as well as in the group from 13 to 18 years of age. With young children the main reasons are most commonly falls from height as well as falls on the same level. There has been observed an increase of head injuries during the holiday period. (JNNN 2014;3(3):121–128)